A novel auxetic metamaterial with enhanced mechanical properties and tunable auxeticity - Zhang, Xiang Yu; Ren, Xin; Zhang, Yi; Xie, Yi Min (Thin-walled structures, 2022)
An auxetic metamaterial composed of novel re-entrant unit cells was proposed. The new re-entrant structure was constructed by adding wedge-shaped parts to the conventional re-entrant structure. Not only can the additional part regulate the structural stiffness during compression but it can also increase the stability of the structure by hindering lateral buckling of the structure, endowing the metamaterial with more significant and stable auxetic behavior in compression. The mechanical and deformation characteristics of the proposed metamaterial were investigated experimentally and numerically. A parametric study was carried out using the validated finite element model to analyze the influence of the size, angle and stiffness of the wedge-shaped part. Due to its improved stiffness and tunability, the proposed auxetic metamaterial has huge potential to be utilized in civil engineering and protection engineering in the form of two-dimensional, three-dimensional and tubular structures. Furthermore, the self-adjusting stiffness property, better stability and enhanced auxeticity make this metamaterial useful for smart materials and intelligent sensors. •The proposed auxetic metamaterial possesses enhanced mechanical properties.•The unit cell was constructed by adding wedge parts to the re-entrant unit.•Large stiffness variation can be achieved without changing auxeticity of the unit.•The stiffness change point was derived and verified.•The self-adjusting stiffness property is promising in smart materials and devices.